KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL DALAM MELAKUKAN PENANGKAPAN (KAJIAN ATAS BEBERAPA PUTUSAN PRAPERADILAN) - Buana, Yudha Cakra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Impementation of the arrest conducted by investigator of official the civillians in the field of forestry as in the pretrial number 02/PID.PRAP/2014/PNJKT.PST, number 10/Pid.Pra/2009/PN.PTK, and number 01/Pid.Pra/2009/PN.Siak not in accordance with applicable regulations and caught applying for a preliminary hearing on the arrest him. The problem in the thesis this is how the authority officials investigating an emplaye of the country’s civil of forestry and doing the arrest and how conciderations of pretrial in accesing the authirty of the investigators of officials in comfornity with the rule of law.After a study by using the method of descriptive or research of the law already that the normative, the source of data is supported by three of the law already, namely the primary data, skunder and decision, after the data collected and analyzed in qualitatively to answer problems in the thesis and the of the conclusion in deducatif.Base on the result of the research that in the pretrial number 02/PID.PRAP/2014/PNJKT.PST and number 10/Pid.Pra/2009/PN.PTK judges declared that the arrests made by civil servant is not in accordance with the criminal procedure of law which has violated article 18 KUHAP of the criminal procedure code, while in the pretrial number 01/Pid.Pra/2009/PN.Siak is legitimate because the judge rejected the request and said the arrest of the applicant is legitimate because the judge is considering arguments which is for the applicant was caught directly in accordance with the article 18 omen (2) KUHAP.Keywords : Investigator Of Official The Civillians – Arrest – Pretrial